A Systematical Examination of the Literature Concerning the Factors That Have an Impact on Employee Performance - Alvin Rafi Alfarissy; Syamsul Hadi Senen (Budapest International Research and Critics University, 2022)
The performance of an employee will certainly affect the activities in a company or organization; therefore, it is important to find out the factors that can cause a decrease or increase in the performance of an employee, in order to optimize the capabilities possessed by each employee. So, the purpose of this study is to find out various factors that are related and can also affect the performance of an employee. The method used in writing this research is a Systematic Literature Review, using Scopus which is the source of data in this study. The data used is limited by the year of publication, starting from 2018 to 2022, the journals used in this study are published in English, and have citations from more than 200 journals. A total of 22 journals were selected for research use. Based on the results obtained in this study, there are various factors that are related and can also improve performance ranging from Leadership, Satisfaction, Motivation, and Employee Resilience, and there are several factors that can also mediate the relationship to Employee Performance.